Manajemen Penyelesaian Pembiayaan Bermasalah Era Pandemi Covid 19 pada Lembaga Perbankan Syariah: - Riski Khaliq; Tuti Anggraini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Sharia Financial Institutions (LKS), both banks and non-banks, have activities to collect funds from the public (customers) and channel these funds through financing and loans, as well as services. After the funds have been channeled by LKS as an investor to the business manager, there are two possibilities: a business that is categorized as smooth because it has good management or poor business management, so that installment payments stop. This study aims to determine how the settlement management carried out by PT Bank SUMUT Syariah in solving problematic financing in the Covid 19 pandemic era and whether the methods used have an impact on all parties concerned. In this study also concluded that the factors that influence the existence of problematic financing are caused by internal factors and external factors which make the bank's control function not functioning properly. So that with these factors, the bank anticipates the steps that are deemed appropriate and in accordance with banking regulations and the Sharia Banking Law as one of the strategies to resolve problematic financing to realize more optimal Islamic banking performance. Keywords: LKS, problematic financing, pandemic Covid-19